O trabalho da mulher no ordenamento jurídico brasileiro: perspectivas do direito trabalhista - Lima , Moara Silva Vaz de (2020)
This work is an academic investigation on the effectiveness of the women’s labor rights as a means to eradicate inequality between men and women in the labor market. Also, it explores the reasons why, even in a democratic state, women continue to suffer many different forms of discrimination in the labor market. Through the inductive and deductive methods, supported by quantitative studies and qualitative analysis, this research aims to analyze the role that women play in society starting from the beginning of the Industrial Revolution process in Western Europe to later analyze the role and the insertion of Brazilian women in the labor market. Subsequently, this work analyzes different perspectives on women’s labor rights, traditional and contemporary, in developed capitalist countries, in international norms and Brazilian norms. Continuing the study, the work deals with some of the challenges that have not yet been overcome in the field of gender equality in the labor market. Finally, the research reveals that these challenges are interconnected and perpetuate discrimination against working women in a process of structural discrimination that requires from Labor Law the deepening of the quality of protection for women in the labor market based on the adoption of an integrated vision with other branches of law and society to, in fact, contribute to accelerate the pace of changes towards substantial equality between men and women.